Production and release of 2-MIB in Pseudanabaena: Effects of growth phases on cell characteristics and 2-MIB yield - Hailing Wang; Lin Li; Shaozhe Cheng; Liang Chen; Haiyang Zhang; Xuezhi Zhang (Ecotoxicology and Environmental Safety, 2024)
2-methylisoborneol (2-MIB), a secondary metabolite produced by cyanobacteria, often causes a musty odour in water, threatening the safety of drinking water supplies. This study investigated the effects of the growth phases on the production of 2-MIB by Pseudanabaena. The effects of cell characteristics on the production and release of 2-MIB were also explored. The total 2-MIB concentration increased during the exponential phase and decreased during the declining phase, which was consistent with the changes in cell density. However, the total 2-MIB yield (1.12–1.27 fg cell−1) of Pseudanabaena did not significantly differ throughout the growth cycle (p > 0.05). Meanwhile, the extracellular 2-MIB yield increased significantly from 0.31 fg cell−1 in the exponential phase to 0.76 fg cell−1 in the declining phase (p < 0.05), and the corresponding proportion of extracellular 2-MIB improved from 25.13% to 59.16% (p < 0.05). The surge in extracellular 2-MIB during the declining phase could be attributed to the breaking of the Pseudanabaena filament, as indicated by the decrease in Dmean during cell ageing. The findings of this study contribute to a more inclusive comprehension and management of musty odour issues resulting from cyanobacteria in the water supply.